Impacts of Some Climatic Variables on the Seasonal Productivity of Aman Rice at Dhaka Region, Central Part of Bangladesh (Journal of Environmental Science and Natural Resources, 2016)
An agro-climatic study was conducted at Dhaka region of Bangladesh using 43 years (1970-2012) of climatic data (daily maximum temperature, seasonal total rainfall, daily average humidity, and daily sunshine hour) to observe the climatic variability and their impacts on the productivity of Aman rice. The average maximum temperature increased by 0.04°C in Aman season in Dhaka region. The average sunshine hours decreased by 0.05 in the season. The average humidity decreased by 0.14% in the season. The average seasonal rainfall increased slightly by 0.09 mm in the season. The Aman rice production increased by 0.03 t ha-1 in the region. The production year 2003 shows highest productivity due to less climatic devastation impact on the seasonal productivity of the rice. The climatic variables impact ( Savg > Havg > Tmax ) implies the seasonal productivity of Aman rice was mostly and inversely correlated with average sunshine (Savg) hour. However, most of the time the production showed increasing trend except some devastating natural calamities in the year of 1988 and 1998 which affected crop production seriously.J. Environ. Sci. & Natural Resources, 8(2): 7-10 2015